Jo Koy : don't make him angry [videorecording (DVD)] - Koy, Jo (Comedy Central Home Video : Distributed by Paramount Pictures, 2009)
Jo Koy, one of today's most gifted young comedians, takes a hilarious and edgy look at everything from America's obsession with road rage to some of his most intimate family moments.